Interaksi Sosial Antara Penghayat Sapta Darma Dengan Komunitas Islam Di Desa - Kevin Ricardo; Lukman Rico (Jurnal Budi Pekerti Agama Buddha, 2023)
According to Munandir, spiritual intelligence is composed of two words, namely "intelligence" and "spiritual". Intelligence is a person's ability to solve the problems they face, especially problems that require the ability of the mind. Various limitations put forward by experts are based on their respective theories. Furthermore, Intelligence can also be interpreted as abilities related to abstractions, the ability to learn something, the ability to handle new situations (Munandir, 2001: 122). In addition to the above understanding, there are a number of experts who argue that spiritual intelligence is the ultimate intelligence or peak intelligence, including Zohar and Marshall in their book entitled: "SQ: Spiritual Intelligence The Ultimate Intelligence"